Project management and its contributions to the implementation of environmental management systems - Leite, Jéssica Pinheiro; Lima, Lucas Alves de Oliveira; Leão, Airton Pereira da Silva; Fonseca, Marcello Pires; Sebastiani, Rafael Teixeira; Silva, Manoel Messias da; Silva, Gustavo Perroni Gomes da; Braga, Thainara da Silva; Silva, Luciano Henrique Pereira da (Seven Editora, 2024)
This research, conducted through interviews with industrial managers through an exploratory study with a qualitative approach, analyzed the effects of project management on the implementation of environmental management systems. The managers emphasized the importance of a structured approach to address the complex challenges of environmental management, highlighting project management as a key tool in this process. The data revealed that project management plays a crucial role in the effective integration of environmental management systems into the daily operations of organizations, demonstrated by the emphasis on clear goal setting, efficient resource allocation, environmental risk identification and mitigation, and effective team coordination. In addition, managers pointed out that project management fostered communication and collaboration between different departments and stakeholders, ensuring proper management of expectations and delivery of results as planned. These results highlight the importance of project management as a strategic approach to effectively integrate environmental management systems into organizational operations, promoting a culture of communication, collaboration, and continuous adaptation, which are fundamental for the success of environmental management in a context of constant change. DOI:https://doi.org/10.56238/sevened2024.007-013